Bioglass/ceria nanoparticle hybrids for the treatment of seroma: a comparative long-term study in rats - Pais, Michael-Alexander; Papanikolaou, Athanasios; Hoyos, Isabel Arenas; Nißler, Robert; De Brot, Simone; Gogos, Alexander; Rieben, Robert; Constantinescu, Mihai A.; Matter, Martin T.; Herrmann, Inge K.; Lese, Ioana (Frontiers in Bioengineering and Biotechnology, 2024)
Background: Seroma formation is a common postoperative complication. Fibrin-based glues are typically employed in an attempt to seal the cavity. Recently, the first nanoparticle (NP)-based treatment approaches have emerged. Nanoparticle dispersions can be used as tissue glues, capitalizing on a phenomenon known as 'nanobridging'. In this process, macromolecules such as proteins physically adsorb onto the NP surface, leading to macroscopic adhesion. Although significant early seroma reduction has been shown, little is known about long-term efficacy of NPs. The aim of this study was to assess the long-term effects of NPs in reducing seroma formation, and to understand their underlying mechanism.Methods: Seroma was surgically induced bilaterally in 20 Lewis rats. On postoperative day (POD) 7, seromas were aspirated on both sides. In 10 rats, one side was treated with NPs, while the contralateral side received only NP carrier solution. In the other 10 rats, one side was treated with fibrin glue, while the other was left untreated. Seroma fluid, blood and tissue samples were obtained at defined time points. Biochemical, histopathological and immunohistochemical assessments were made.Results: NP-treated sides showed no macroscopically visible seroma formation after application on POD 7, in stark contrast to the fibrin-treated sides, where 60% of the rats had seromas on POD 14, and 50% on POD 21. At the endpoint (POD 42), sides treated with nanoparticles (NPs) exhibited significant macroscopic differences compared to other groups, including the absence of a cavity, and increased fibrous adhesions. Histologically, there were more macrophage groupings and collagen type 1 (COL1) deposits in the superficial capsule on NP-treated sides.NPs not only significantly reduced early manifestations of seroma and demonstrated an anti-inflammatory response, but they also led to increased adhesion formation over the long term, suggesting a decreased risk of seroma recurrence. These findings highlight both the adhesive properties of NPs and their potential for clinical therapy.